Bacterial cystitis in females: A review - A E Aghaji; F O Ugwumba (International Journal of Medicine and Health Development, 2004)
Aim: To review the aetiology, clinical features, investigations and treatment of bacterial cystitis in females. Materials and Methods: A medline search was carried out and the literature reviewed in line with the aims for meaningful findings. Results: Bacterial cystitis is classified into uncomplicated and complicated varieties. Uncomplicated cystitis occurs in an otherwise healthy patient without structural or functional abnormalities in the urinary tract. Complicated cystitis occurs in compromised patient with structural or functional abnormalities that enhance infection acquisition and reduce efficacy of therapy. Bacterial cystitis occurs with varying frequency in females from the neonatal period to old age. Conclusion: Bacterial cystitis is a common and distressing, clinical problem in females, and may be recurrent especially in young women or those with urinary tract anomalies. Risk factors exist, with some being preventable. An appreciation of predisposing factors, aetiopathogensis, diagnostic and treatment modalities are useful. Preventive strategies need to be emphasized in our environment.